2018
DOI: 10.18773/austprescr.2018.045
|View full text |Cite
|
Sign up to set email alerts
|

Drugs for benign prostatic hypertrophy

Abstract: Benign prostatic hyperplasia is a common condition. It can cause problems with urine storage and voiding, and the severity of symptoms may be unrelated to the size of the prostate. When drug treatment is required, benign prostatic hyperplasia can be managed with monotherapy or combination therapy. Most patients are managed with selective alpha blockers. Patients with larger prostate volumes may benefit from a 5-alpha-reductase inhibitor, usually in combination with an alpha blocker. Medical therapy for benign … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…This finding is supported by the work Huang Shei-Wei et al and Macey et al 11,12 Dizziness and postural hypotension are most common adverse drug reaction in both medical management group medical but urinary incontinence and decreased libido was common in silodosin and dutasteride. This finding is supported by the work of Zaman Huri et al and Jiwrajka et al 14,15 In our study we have observed that quality of life score was improved in all three group but the improved in QOL for TURP group was better than medical management.…”
Section: Resultssupporting
confidence: 89%
“…This finding is supported by the work Huang Shei-Wei et al and Macey et al 11,12 Dizziness and postural hypotension are most common adverse drug reaction in both medical management group medical but urinary incontinence and decreased libido was common in silodosin and dutasteride. This finding is supported by the work of Zaman Huri et al and Jiwrajka et al 14,15 In our study we have observed that quality of life score was improved in all three group but the improved in QOL for TURP group was better than medical management.…”
Section: Resultssupporting
confidence: 89%
“…Ablative surgery, α Blockers, 5-α Reductase inhibitors (5-ARIs), and a combination of α blockers and 5-ARIs have been inaugurated to treat BPH condition [ 28 ] but also presents the risk of ejaculatory dysfunction, hypotension, tachycardia, decreased semen count [ 29 ]. So, at present effective treatable drug is still unattained.…”
Section: Introductionmentioning
confidence: 99%
“…BPH and resultant LUTS affect men as they age, which adversely impacts on their quality of life [1][2][3]. Currently recommended treatment options include watchful waiting, medical therapy and surgery [4][5][6]. Medical therapy for LUTS secondary to BPH encompasses a wide range including 5areductase inhibitors (5ARIs), a-blockers (ABs), antimuscarinics, b 3 -agonists, and phosphodiesterase type 5 inhibitors.…”
Section: Introductionmentioning
confidence: 99%